A numerical method for solving an inverse thermoacoustic problem - Kabanikhin, S. I.; Krivorot’ko, O. I.; Shishlenin, M. A. (Numerical analysis and applications, 2013)
In this paper, we consider an inverse problem of determining the initial condition of an initial boundary value problem for the wave equation with some additional information about solving a direct initial boundary value problem. The information is obtained from measurements at the boundary of the solution domain. The purpose of our paper is to construct a numerical algorithm for solving the inverse problem by an iterative method called a method of simple iteration (MSI) and to study the resolution quality of the inverse problem as a function of the number and location of measurement points. Three two-dimensional inverse problem formulations are considered. The results of our numerical calculations are presented. It is shown that the MSI decreases the objective functional at each iteration step. However, due to the ill-posedness of the inverse problem the difference between the exact and approximate solutions decreases up to some fixed number k min , and then monotonically increases. This shows the regularizing properties of the MSI, and the iteration number can be considered a regularization parameter.